Effect of Fly Ash and Silica Fume on compressive strength, sorptivity and carbonation of SCC - Turk, Kazim; Karatas, Mehmet; Gonen, Tahir (Korean Society of Civil Engineers-Ksce, 2013)
In this paper, ASTM C 618 Class F Fly Ash (FA) at 25%, 30%, 35% and 40% and Silica Fume (SF) at 5%, 10%, 15% and 20% replacement of Portland Cement (PC) CEM I 42.5 in SCC was used to evaluate the effect of types and quantity of powder additions on compressive strength and permeations properties of SCC. To this end, eight types of SCC were designed, in comparison with Vibrated Traditional Concrete (VTC). The results indicated that SCC specimens with SF15 had the highest compressive strength with 73.87 MPa for 130 days. The sorptivity values of SCC specimens with FA and SF were lower than those of VTC specimens regardless of type and quantity of powder additions. On the other hand, the carbonation resistance of VTC was higher than that of SCC specimens containing both SF and FA for all accelerated carbonation periods. Consequently, it can be said that type and quantity of powder additions had an important effect on the correlation among the compressive strength and permeation properties of SCC.
Keywords: self-compacting concrete; mineral admixtures; compressive strength; sorptivity; carbonation